PENGARUH MODEL CIRCUIT LEARNING BERBANTUAN MEDIA CARRD.CO TERHADAP HASIL BELAJAR KOGNITIF PENDIDIKAN PANCASILA - YULIYANTI, WULAN; JAMALUDIN, UJANG; BAHRUDIN, FEBRIAN ALWAN (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This research was conducted in response to the results of field observations at SMA Negeri 5 Serang City, which still has minimal application of interactive learning models. Therefore, the students frequently experience boredom and lack enthusiasm for their studies. This study aimed to answer whether or not the circuit learning model assisted by Carrd.co media has an effect on cognitive learning outcomes of Pancasila Education. This study used a quasi-experimental method with a nonequivalent control group design, one type of quantitative research. A sample of 100 students, identified as class XI A1 (experimental) and XI S2 (control), were tested using pre-test and post-test. This showed the critical importance of selecting a suitable sample and a reliable and valid measurement instrument to guarantee that the research results accurately describe the effect of the learning model. A test technique was used to measure students' cognitive learning outcomes, with a pre-test and post-test instrument totaling 26 multiple-choice questions. The data analysis techniques utilized in this research included the normality test, homogeneity test, difference test (Wilcoxon test), hypothesis test (Mann-Whitney test), and n-gain test. The results of the analysis showed the value of Asymp. Sig (2-tailed) of 0.001 <0.05. Consequently, it can be inferred that the "Ha hypothesis" was accepted and the "H0 hypothesis" was rejected. This implies that the cognitive learning outcomes of Pancasila Education in class XI students of SMA Negeri 5 Serang City were influenced by the circuit learning model, which was facilitated by Carrd.co media, concerning the learning material of the Meaning and Relationship of the Pancasila precepts. ABSTRAKPenelitian ini dilatarbelakangi melalui hasil observasi lapangan, SMA Negeri 5 Kota Serang masih minim penerapan model pembelajaran interaktif, sehingga peserta didik cenderung bosan dan kurang semangat belajar. Fokus masalah pada penelitian ini bertujuan untuk menjawab ada atau tidaknya pengaruh model circuit learning berbantuan media carrd.co terhadap hasil belajar kognitif Pendidikan Pancasila. Penelitian ini menggunakan metode quasi-eksperimen dengan desain nonequivalent control grup design yang merupakan salah satu jenis penelitian kuantitatif, sampel 100 peserta didik, yaitu kelas XI A1 (eksperimen) dan XI S2 (kontrol), yang diuji menggunakan pre-test dan post-test. Hal ini menunjukkan bahwa pemilihan sampel yang sesuai, disertai dengan instrumen pengukuran yang valid dan reliabel, sangat penting untuk memastikan hasil penelitian dapat menggambarkan pengaruh model pembelajaran secara akurat. Dalam rangka mengukur tes hasil belajar kognitif peserta didik digunakan teknik tes dengan instrumen pre-test dan post-test berjumlah 26 soal pilihan ganda. Penelitian ini menggunakan teknik analisis data berupa uji normalitas, uji homogenitas, uji hasil beda (Uji wilcoxon), uji hipotesis (Uji mann-whitney), dan uji n-gain. Hasil analisis menunjukkan nilai Asymp. Sig (2-tailed) sebesar 0,001 < 0,05. Dengan begitu dapat disimpulkan bahwa “Hipotesis Ha diterima dan H0 ditolak yang artinya terdapat pengaruh model circuit learning berbantuan media Carrd.co terhadap hasil belajar kognitif Pendidikan Pancasila pada peserta didik kelas XI SMA Negeri 5 Kota Serang pada meteri pembelajaran Makna dan Keterkaitan sila-sila Pancasila.”